1999
DOI: 10.1557/proc-575-259
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Fuel Cell Testing of Radiation-Grafted Psi Membranes

Abstract: We have demonstrated earlier the useful performance of our PSI radiation-grafted membranes in terms of the current-voltage characteristics of 30 cm2 active area fuel cells containing these membranes and their long-term testing over 6,000 h at 60 °C. We report here on testing of PSI radiation-grafted membranes in these fuel cells at 80 °C and in short stacks comprised of two or four 100 cm2 active area cells. The in-situ degradation of membranes has been investigated by characterizing membranes both before test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Among these membranes being developed, radiation-grafted membranes have become attractive materials because of their high proton conductivity and relatively lower cost. The longest durability of the PEMFC with the radiation-grafted membranes has reported to be 10,000 h, 3 and the price of the radiation-grafted membranes is considerably lower than that of the commercial perfluorosulfonic membranes. In addition, the radiation-grafted membranes have also been used in electrodialysis, elec-trosynthesis, protein extraction, and purification and recovery in etching processes.…”
Section: Introductionmentioning
confidence: 99%
“…Among these membranes being developed, radiation-grafted membranes have become attractive materials because of their high proton conductivity and relatively lower cost. The longest durability of the PEMFC with the radiation-grafted membranes has reported to be 10,000 h, 3 and the price of the radiation-grafted membranes is considerably lower than that of the commercial perfluorosulfonic membranes. In addition, the radiation-grafted membranes have also been used in electrodialysis, elec-trosynthesis, protein extraction, and purification and recovery in etching processes.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated testing of the oxidative stability of candidate membranes can be carried out by exposure to hydrogen peroxide solutions containing redox active species. In a previous work,7 we showed a qualitative correlation between the retention of membrane properties in such accelerated tests and the membrane lifetime and stability in PEFCs.…”
Section: Introductionmentioning
confidence: 57%
“…Some films were preirradiated in air with a 60 Co γ‐irradiation source; others were preirradiated in an air or nitrogen atmosphere with an electron‐beam source. We optimized several parameters in our irradiation conditions earlier to achieve a maximum grafting yield by minimizing radical consumption through combination or degradation reactions 4, 5, 7, 16. For example, samples were cooled by being placed on dry ice during radiation processing, and thermally sensitive colorimetric indicator strips confirmed that the macroscopic temperature of the samples remained subambient.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations